Pengaruh Pemasaran Digital Terhadap Peningkatan Pendapatan UMKM di Kecamatan Polewali Kabupaten Polewali Mandar - Nurdiana; Ramida; Mustari; Muhammad Dinar; Tuti Supatminingsih (Department of Economics Education, Faculty of Economics, Universitas Negeri Makassar, 2022)
The aim of this study is to determine the effect of digital marketing on increasing UMKM’s income in Polewali district, Polewali Mandar regency. This research was categorized as qualitative descriptive research. 12345 Program Studi Pendidikan Ekonomi, Fakultas Ekonomi dan Bisnis, Universitas Negeri Makassar the data were collected through observation and distributing questionnaires. The UMKM population was 726 respondents consisting of small businesses amounted to 636 respondents, 77 micro businesses, 13 small businesses and 42 respondents were selected as sampel. In this study using a sampling technique that is proportionate sampling. Data analysis used descriptive statistics and inferential statistics. The results of the study showed that they were simultaneous, digital marketing variables have a positive and significant effect on the income of UMKM in Polewali district. The determinant test of R in this study resulted in a value of determinant R 0.214 showing the level of the influence of digital marketing variables on income 21%, with the rest explained by other variables human resources, capital, and so on.